Outcome Based Education (OBE) System for Theological College - Dhandi, Gabriel (MAHABBAH: Journal of Religion and Education, 2025)
Outcome Based Education (OBE) is an education system that focuses on learning outcomes that are measurable, directed, and relevant to the needs of the industrial world in the Industrial Age 4.0. The purpose of this study is to offer the application of the OBE system in designing and developing curriculum at the College of Theology in order to bridge the gap between the abilities or competencies of graduates and the needs of the modern Christian community. The method used in this research is a literature study, which is to collect library data sources and previous research, then explore them to be presented to support this research. The results of this study show that the OBE system is very effective in improving the quality and quality of education, producing graduates who are competent in their fields and preparing them to face challenges in the Industrial Age 4.0. The implementation of the OBE system into curriculum development at Theological College will certainly help improve the quality of education, be able to compete with other universities, and raise Theological College’s reputation. The conclusion of this research is that the OBE system is feasible to be applied in developing the curriculum used by Theological College.